Time-division-multiplexed interrogation of fibre Bragg grating sensors using laser diodes - Wilson, A.; James, Stephen W.; Tatam, Ralph P. (Institute of Physics (IOP), 2001)
An intensity-based technique for the interrogation of fibre Bragg grating sensors is described. The technique utilizes two longitudinal modes of a single, pulsed laser diode as a dual-wavelength source for grating illumination. Time-division-multiplexed addressing of sensor arrays in serial and tree topologies is also demonstrated.
Keywords: laser diode optical fibre fibre Bragg gratings time-division multiplexing phase mask fiber system